PROGRAM REHABILITASI SOSIAL DI LAPAS NARKOTIKA KELAS II A NUSAKAMBANGAN : SINERGI DAN PENDEKATAN HOLISTIK DALAM MENDUKUNG PEMULIHAN WARGA BINAAN PERMASYARAKATAN - Ria Alfiati; Azis Wahyono (Kampus Akademik Publiser, 2025)
Drug abuse is a serious threat to public health and national security in Indonesia, requiring a comprehensive approach. This study aims to analyze the implementation of the social rehabilitation program at the Class II A Nusakambangan Narcotics Prison, focusing on cross-institutional synergy and a holistic approach to supporting the recovery of inmates. The research method uses a qualitative descriptive approach through observation and in-depth interviews with prison officers, inmates, and rehabilitation program facilitators. The results show that the social rehabilitation program at the Class II A Nusakambangan Narcotics Prison applies a holistic approach that integrates four main aspects: (1) physical aspects through detoxification and medical treatment; (2) psychosocial aspects through group and individual counseling; (3) mental and spiritual aspects through religious activities and meditation; and (4) independence aspects through vocational training. Synergy between the Prison, the National Narcotics Agency (BNN), the Ministry of Social Affairs, the Ministry of Health, and related institutions is the key to the success of this program. This comprehensive rehabilitation program focuses not only on physical recovery, but also on character and skills development to prepare inmates to become productive individuals and be able to reintegrate into society, while reducing the risk of drug recidivism.